A New Anthraquinones from Cassia fistula and its Cytotoxicity - Li, Lan; Xu, Wen-Xiu; Liu, Chun-Bo; Zhang, Cheng-Ming; Zhao, Wei; Shang, Shan-Zhai; Deng, Liang; Guo, Ya-Dong (Asian Journal of Chemistry, 2015)
A new anthraquinone, cassiquinone A (1), was isolated from the stems of Cassia fistula. Its structure was elucidated by spectroscopic methods, including extensive 1D- and 2D NMR techniques. Compound 1 was tested for its cytotoxicity against five human tumor cell lines (NB4, A549, SHSY5Y, PC3 and MCF7) and compound 1 showed high cytotoxicity against A549 and MCF7 cell with IC50 values of 8.2 and 6.5 μM, respectively.